Biocatalysis and biomass conversion: enabling a circular economy. (24th July 2020) - Sheldon, Roger A.
Abstract : This paper is based on a lecture presented to the Royal Society in London on 24 June 2019. Two of the grand societal and technological challenges of the twenty-first century are the 'greening' of chemicals manufacture and the ongoing transition to a sustainable, carbon neutral economy based on renewable biomass as the raw material, a so-called bio-based economy. These challenges are motivated by the need to eliminate environmental degradation and mitigate climate change. In a bio-based economy, ideally waste biomass, particularly agricultural and forestry residues and food supply chain waste, are converted to liquid fuels, commodity chemicals and biopolymers using clean, catalytic processes. Biocatalysis has the right credentials to achieve this goal. Enzymes are biocompatible, biodegradable and essentially non-hazardous. Additionally, they are derived from inexpensive renewable resources which are readily available and not subject to the large price fluctuations which undermine the long-term commercial viability of scarce precious metal catalysts. Thanks to spectacular advances in molecular biology the landscape of biocatalysis has dramatically changed in the last two decades. Developments in (meta)genomics in combination with 'big data' analysis have revolutionized new enzyme discovery and developments in protein engineering by directed evolution have enabled dramatic improvements in their performance. These developments have their confluence in the bio-based circular economy. This article is part of a discussion meeting issue 'Science to enable the circular economy'.